Going large scale: The Polling Conference process for participatory constitution making in Turkey. Issue 4 (December 2014) - Baburoglu, Oguz N; Goker, Gulru Z
This paper narrates the story of large-scale, nation-wide intervention for participatory constitution making in Turkey. The process of democratic involvement in the making of Turkey's new Constitution has been an action research engagement since 2007 for the authors of this paper. In due process, a deliberative democracy-inspired large-scale conferencing, i.e., the Polling Conference [ Tarama Konferansı ], was designed. Ordinary, unaffiliated citizens and local nongovernmental organization (NGO) members participated in the constitution-making process via attending these conferences across the nation. Reflecting upon Turkey's first participatory constitution-making initiative and our intervention, we came to develop certain emergent themes, decisions and actions necessary for the successful realization of large-scale action research in polarized political contexts. These themes range from the establishment of a convening body and legitimate links to decision making and society, to the industrious preparation of a social-ecology on local and national levels. Our intervention is thoroughly embedded in the Turkish context; nevertheless, we came to develop a thematic approach that could set an example to nation-wide participatory initiatives in similar democratic trajectories.